(untitled) (The International Journal for Scientific Research, 2025)
This study aims to describe types of question in Arabic and their counterparts in English to find out the similarities and differences between them, especially in Surah Al Kahf. This study is a complex and challenging one, because Surah Al-Kahf is a long and complex surah, and it contains a wide variety of questions. Some of these questions are rhetorical, some are open-ended, and some are closed-ended. Additionally, the English language is very different from the Arabic language, and this can make it difficult to accurately translate and understand the meaning of the questions in Surah Al-Kahf. This paper deals with types of Surah Al-Kahf’s questions and their realization in English. It can provide insights of the Quran’s rhetorical and communicative strategies. It can also improve the translation of this important surah into English. The study can identify the different types of questions, examine their translations in English, and analyze the impact of translation on the text’s meaning and communicative effect. Comparative analysis of different translations can also help to identify areas for improvement.